CD226+ B cells in primary Sjögren’s syndrome: a key player in clinical manifestations and disease pathogenesis - Zhao, Ping; Song, Saizhe; Zhang, Song; Peng, Cheng; Cheng, Wei; Chang, Xin; Xie, Changhao; Hu, Zhongli; Liu, Cuiping (Frontiers in immunology, 2025)
Primary Sjögren's syndrome (pSS) is a systemic autoimmune disorder characterized by lymphocytic infiltration of exocrine glands, leading to sicca symptoms and systemic complications. CD226, a co-stimulatory receptor implicated in the pathogenesis of multiple autoimmune diseases including systemic lupus erythematosus (SLE), rheumatoid arthritis(RA), and pSS, regulates immune cell activation. However, the specific role of CD226+ B cells in pSS pathogenesis remains unclear. This study aims to elucidate the functional contribution of CD226 B cells to pSS development and their clinical relevance. The percentages of CD226 on T cells, B cells, CD56 NK cells and CD14 monocytes in the peripheral blood(PB) of pSS patients and healthy controls (HCs) were detected by flow cytometry.Multicolor flow cytometry was employed to examine the distribution of CD226 in B cell subsets of pSS patients, as well as the expression levels of co-stimulatory molecules, activation and proliferation markers, immunoglobulins, and pro-inflammatory cytokines on both CD226 B cells and CD226 B cells. Multicolor immunofluorescence staining was applied to detect the co-expression of B cells and CD226 in the salivary gland of pSS patients.Microarray analysis was conducted to analyze the transcriptomic profiles of sorted CD226 CD19 B cells and CD226 CD19 B cells. CD226 expression in the peripheral blood of pSS patients was significantly increased on T cells, CD19 B cells and CD14 monocytes, but significantly decreased on CD56 NK cells.We identified a distinct CD226 CD19 B cell subset that exhibited pathogenic features in pSS. CD226 was significantly upregulated on B cells in the peripheral blood and salivary glands of pSS patients.CD226 CD19 B cell showed a stronger correlation with clinical features, disease activity, and prognosis in pSS patients.The ROC curve demonstrated that CD226 CD19 B cell exhibited significant diagnostic capability to distinguish pSS patients from healthy controls and to differentiate disease activity.This subset also exhibited heightened activation and pro-inflammatory phenotypes. CD226 B cells are expanded in pSS, strongly correlating with clinical manifestations and disease activity. These cells display enhanced effector profiles (activation, cytokine/immunoglobulin production) and demonstrate diagnostic utility. Our findings identify CD226 B cell as a pathogenic driver in pSS, positioning CD226 as a promising novel therapeutic target and biomarker.